Disparity of innate immunity-related gene effects on asthma and allergy on Karelia - Zhang, Guicheng; Candelaria, P.; Mäkelä, J.; Khoo, S.; Hayden, M.; von Hertzen, L.; Laatikainen, T.; Vartiainen, E.; Goldblatt, J.; Haahtela, T.; Lesouëf, N. (2011)
Background: We investigated the interactive effects of 11 innate immunity-related genes (IL10, IL12b, IL8, TLR2, TLR4, CD14, IFNGR, CC16, IFNg, CMA1, and TGFB) and four IgE response genes (IL4, IL13, IL4RA, and STAT6) with 'Western' or 'Eastern' environments/lifestyles on asthma and allergy in Karelian children. Methods: Karelian children (412 Finnish and 446 Russian) were recruited and assessed for a range of allergic conditions, with 24 single-nucleotide polymorphisms genotyped in 15 genes. Results: The genotype-phenotype relationships differed in Finnish and Russian Karelian children. The interaction between polymorphisms and the variable representing 'Western' and 'Eastern' environments/lifestyles was significant for IL10-1082 (p=0.0083) on current rhinitis, IL12b 6408 on current conjunctivitis (p=0.016) and atopy (p=0.034), IL8 781 on atopic eczema (p=0.0096), CD14 -550 on current rhinitis (p=0.022), IFNgR1 -56 on atopic eczema(p=0.038), and STAT6 2964 on current itchy rash (p=0.037) and total serum IgE (p=0.042). In addition, the G allele of IL13 130 was associated with a lower level of total serum IgE in Finnish (p=0.003) and Russian (p=0.01) children and overall (pooling the two populations together, p=0.00006). After adjusting for multiple tests, the association between IL13 130 and IgE and the interactive effects of IL10-1082 on current rhinitis and IL8 781 on atopic eczema were significant by controlling a false-positive rate of 0.05 and 0.10, respectively. Conclusions: Living in an Eastern vs. Western environment was associated with a different genetic profile associated with asthma and allergy in the Karelian populations. © 2011 John Wiley & Sons A/S.